2023
DOI: 10.1364/ao.485006
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization of line patterns in extreme ultraviolet lithography using machine learning and a simulated annealing algorithm

Abstract: Resolution, line edge/width roughness, and sensitivity (RLS) are critical indicators for evaluating the imaging performance of resists. As the technology node gradually shrinks, stricter indicator control is required for high-resolution imaging. However, current research can improve only part of the RLS indicators of resists for line patterns, and it is difficult to improve the overall imaging performance of resists in extreme ultraviolet lithography. Here, we report a lithographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…At present, researchers have begun to use AI/ML to improve the quality of photoresist patterns, mainly adopting modeling and optimization methods based on multilayer feed-forward neural networks (MFNNs). 29,30,40,41 However, the accuracy of the MFNN model needs to be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…At present, researchers have begun to use AI/ML to improve the quality of photoresist patterns, mainly adopting modeling and optimization methods based on multilayer feed-forward neural networks (MFNNs). 29,30,40,41 However, the accuracy of the MFNN model needs to be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML) is one of the most intelligent and cutting-edge modeling methods in artificial intelligence (AI), which studies how to use computers to simulate or implement human learning activities . Recently, researchers have begun to pay attention to an ML method, that is, long short-term memory (LSTM) networks, and use them to build predictive models for fuel cells, financial market, stock market, soft sensor, wind power, photovoltaic power, and solar irradiance. It is worth noting that many scholars have demonstrated that the LSTM network with long-term memory function has better prediction ability than multilayer perceptron neural network (MPNN), ,, which is one of the most commonly used ML modeling methods. Therefore, in this article, we use an LSTM network to establish a lithographic imaging prediction model.…”
Section: Introductionmentioning
confidence: 99%
“…Lithography is an imaging technology that transfers the designed circuit patterns to the wafer, which is considered to be the most critical process in chip manufacturing . At present, extreme ultraviolet (EUV) lithography and electron beam lithography (EBL) are regarded as two promising candidate technologies to realize high-resolution circuit patterns in a chip. However, a large number of research results show that the imaging performance of the two lithography technologies is seriously affected by exposure, baking, development, and other process conditions. As the feature size gradually decreases, the impact on lithography imaging will be more significant. Optimizing and controlling the lithographic process conditions have become an urgent need.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, machine learning methods are gradually being applied to the field of lithography, in which the most widely used is the multilayer feed-forward neural network (MFNN). At present, researchers have proposed process optimization approaches 5,21,[29][30][31][32][33] based on MFNN to obtain matching process conditions. Nevertheless, the MFNN model requires a large number of data sets to achieve high-precision predictive performance.…”
Section: Introductionmentioning
confidence: 99%